A Security Architecture for Cloud Computing Alliance - Jun, Zhao (Recent Advances in Electrical & Electronic Engineering, 2017)
Background: Credibility problems in the cloud service are very important issues in cloud computing alliance. Methods: By using the small world model in complex networks, a relationship model of cloud computing alliance can be established; defense game model is established under the cloud alliance by game theory; by combining the self-organization of small world model with self-constraint binding of game model, offensive and defensive game model of incomplete information is realized. Through the simulation experiments, they verify trusted resource management functions in the cloud computing alliance. Results: Moreover, by using unsupervised and supervised management conditions, access requesting nodes for cloud service and comparative analysis of respondents in the cloud service get a better resource management effect.
Keywords: cloud computing alliance